The Quality of Friendships in Students Who Experience Trust Problems - Astriani, Ririn; Saut H. Hutahaean, Erik; Fahrudin, Adi (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Conflicts between individuals often clash with friendships; one of the causes is trust issues. Trust issues related to how one thinks about others; The existence of a negative mindset (negative thinking) to friends can damage trust and hurt friendship relationships. This negative mindset can affect the quality of friendships among students. Objective: This study aims to analyze the quality of friendships in students who experience trust problems. Method: One hundred and fifteen respondents have/are experiencing trust problems filling out this questionnaire. The friendship quality category was analyzed using simple correlation and regression analysis. Result and Discussion: The results of this study show that negative thinking patterns and friendship quality in students have a negative correlation. Conclusion:  The lower the negative thinking, the higher the quality of the company, and vice versa; the higher the negative thinking, the lower the level of friendship.